2016
DOI: 10.1002/pds.4090
|View full text |Cite
|
Sign up to set email alerts
|

Can social media data lead to earlier detection of drug‐related adverse events?

Abstract: PurposeTo compare the patient characteristics and the inter‐temporal reporting patterns of adverse events (AEs) for atorvastatin (Lipitor®) and sibutramine (Meridia®) in social media (AskaPatient.com) versus the FDA Adverse Event Reporting System (FAERS).MethodsWe identified clinically important AEs associated with atorvastatin (muscle pain) and sibutramine (cardiovascular AEs), compared their patterns in social media postings versus FAERS and used Granger causality tests to assess whether social media posting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 9 publications
2
53
0
Order By: Relevance
“…The qualitative exploratory analysis of the SDRs detected earlier showed that the events were related to serious as well as patient related symptoms. This finding are in light with recent studies [14] which addressed the question on earlier detection of drug-related adverse events in the social media as compared to FDA Adverse Event Reporting System (FAERS). The findings highlighted some of the promises of social media data sources for detecting early AE reports patterns compared to conventional pharmacovigilance sources and showed that social media AE reports helped predict the occurrence of FAERS reports several months later for one of the two drugs that were studied.…”
Section: Discussionsupporting
confidence: 52%
“…The qualitative exploratory analysis of the SDRs detected earlier showed that the events were related to serious as well as patient related symptoms. This finding are in light with recent studies [14] which addressed the question on earlier detection of drug-related adverse events in the social media as compared to FDA Adverse Event Reporting System (FAERS). The findings highlighted some of the promises of social media data sources for detecting early AE reports patterns compared to conventional pharmacovigilance sources and showed that social media AE reports helped predict the occurrence of FAERS reports several months later for one of the two drugs that were studied.…”
Section: Discussionsupporting
confidence: 52%
“…The examination of SM utility in identifying AEs and SDRs has been previously performed by multiple groups, using various approaches. Some authors have concluded that SM should be further considered as a potential SD tool, while others concluded that SM shows a poor performance in AE and SDR identification . Although we count this work among the former group, we do not disagree with the core conclusions of the latter.…”
Section: Discussionmentioning
confidence: 52%
“…Some authors have concluded that SM should be further considered as a potential SD tool, 17,18 while others concluded that SM shows a poor performance in AE and SDR identification. 19,20 Although we count this work among the former group, we do not disagree with the core conclusions of the latter. Namely, we agree that SM cannot be used as a stand-alone data source and should not replace other pharmacovigilance activities.…”
Section: Discussionmentioning
confidence: 56%
“…Social media generate patient-centric data, which is typically unfiltered and unchecked, and can use the incorrect terms, or refer to diagnoses that are based on Internet research rather than confirmed diagnoses from healthcare professionals (risk of misinformation). Social media disclosures are also conditioned by the disclosers gender and cultural background, resulting in differences in linguistic [91,157]. Hence, pharmacovigilance practice could benefit from empowered, motivated and knowledgeable patients, through increased public awareness of pharmacovigilance, through the closer engagement of pharmacovigilance stakeholders (regulatory authorities, industry) with patients, through the diffusion of scientific knowledge regarding health, illness, therapy and medicines, and through the further strengthening of health support networks and communities.…”
Section: Value/utility Of Social Media As Knowledge Sources For Pharmmentioning
confidence: 99%